PENYULUHAN PENGAWASAN DAN PARTISIPASI PEMILIH PEMULA DALAM PEMILIHAN UMUM TINGKAT SEKOLAH MENENGAH KEJURUAN (SMK) - Liany, Lusy; Jufri, Ely Alawiyah; Umardani, Mohammad Kharis (Jurnal Balireso: Jurnal Pengabdian pada Masyarakat, 2018)
Elections are a decisive momentum in the life of democracy. This democratic party will determinenot only the head of state but also the representatives of the people who will sit in the legislativebody. The whole process certainly will not work without the participation of voters throughoutIndonesia, especially in this case the novice voters. Beginner voters have always been the center ofattention ahead of elections. Besides because they are a young generation who have an emotionalcharacter that is still unstable, coupled with the lack of experience in deciding political choices.Therefore, often the political behavior of young voters is not constant beginner even does not playan active role in the election. For this reason, the provision of material about the participation ofnovice voters in the election to the students is absolutely necessary so that the students can knowhow to play an active role in the election so as to apply it in the life of the nation and state.